Transformasi Guru PPKn SMPN 17 Medan: Dari Pengajar Menjadi Teladan Moral di Era Digital - Nurul Fazira Damanik; Friska Rehulina Br Ginting; Ameytia Rizka Aulia; Rachel Rosalina Sirait; Alvin Putra Hariando Manik; Jamaludin Jamaludin (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study examines the transformation of the role of PPKn teachers at SMPN 17 Medan from mere educators to moral role models in the digital era. This study, which used qualitative methods through observation and interviews, uncovered insights from PPKn teacher Mrs. Dina Noviana and her students. The study revealed that teachers must navigate the complexity of the digital environment, recognizing its positive and negative impacts on students’ character development. Teachers are now tasked with not only delivering curriculum content but also acting as role models in moral behavior, especially in online interactions. The study’s findings suggest that effective moral guidance is essential, balancing curriculum delivery with instilling ethical values. Students expressed appreciation for teachers who demonstrated positive attitudes and modeled appropriate behavior in both academic and digital settings. This study underscores the importance of PPKn educators evolving with digital trends, becoming relevant moral guides who are able to prepare students for future challenges while fostering character in a rapidly changing digital landscape. This study emphasizes that the role of PPKn teachers is essential in instilling ethical values, morality, and integrity, thus shaping future community leaders. Ultimately, these findings suggest the need for educators to adapt and refine their approaches to be effective in the digital era.